Does Husband/Partner Matter in Reduce Women’s Risk of Worries?: Study of Psychosocial Burden of COVID-19 in Indonesia - *Hario Megatsari1 , Agung Dwi Laksono2 , Yeni Tri Herwanto3 , Kinanty Putri Sarweni4 , Rachmad Ardia (Indian Journal of Forensic Medicine & Toxicology, 2021)
Several previous studies have found that women are more susceptible to psychosocial burden than men.The study was aimed at analyzing the influence of having a husband/partner on the psychosocial burdenof COVID-19 among women in Indonesia. The study involved 5,061 women collected through a rapidonline survey. The psychosocial burden was reviewed based on worries level on 5 aspects of daily life,namely economic, religious, educational, employment, and social aspects. Four independent variables wereincluded in the analysis, including husband/partner ownership, age group, education level, and employmentstatus. A multivariate test using the binary logistic regression was done at the final stage. The results showthat women who have a husband/partner have a risk of 1.377 times compared to women who do not havehusbands/partners to experience worries. Women in the 40-49 age group had 0.630 times the risk of womenwith ? 19 age groups to experience worries. Meanwhile, women with the ? 50 age groups had a 0.327times risk than women with the ? 19 age groups for experiencing worries. Women with higher educationhave a risk of 0.610 times compared to women with secondary education for experiencing worries. It couldbe concluded that having a soulmate is a risk factor for women to experience the psychosocial burden ofCOVID-19 in Indonesia. The analysis also found that younger age and lower education were risk factors forwomen to experience the psychosocial burden of COVID-19 in Indonesia.